Assessing complex problem-solving skills with multiple complex systems - Greiff, Samuel; Fischer, Andreas; Stadler, Matthias; Wüstenberg, Sascha (Thinking & reasoning, 2015)
In this paper we propose the multiple complex systems (MCS) approach for assessing domain-general complex problem-solving (CPS) skills and its processes knowledge acquisition and knowledge application. After defining the construct and the formal frameworks for describing complex problems, we emphasise some of the measurement issues inherent in assessing CPS skills with single tasks (i.e., fixed item difficulty, low or unknown reliability, and a large impact of random errors). With examples of the MicroDYN test and the MicroFIN test (two instances of the MCS approach), we show how to adequately score problem-solving skills by using multiple tasks. We discuss implications for problem-solving research and the assessment of CPS skills in general.